Carbon Responsibility and Embodied Emissions : Theory and Measurement. - Rodrigues, Joo F. D. (Routledge studies in ecological economics., 2010)
Investigates environmental indicators accounting for indirect emissions (as embodied in international trade) within the framework of input-output analysis. This book introduces an indicator of environmental responsibility derived from upstream emissions embodied in final demand and downstream emissions embodied in primary inputs.